C4 Photosynthesis (The Effects of Leaf Development on the CO2-Concentrating Mechanism and Photorespiration in Maize). - Dai, Z. (1995)
The effect of O2 on photosynthesis was determined in maize (Zea mays) leaves at different developmental stages. The optimum level of O2 for maximum photosynthetic rates was lower in young and senescing tissues (2-5 kPa) than in mature tissue (9 kPa). Inhibition of photosynthesis by suboptimal levels of O2 may be due to a requirement for functional mitochondria or to cyclic/pseudocyclic photophosphorylation in chloroplasts; inhibition by supraoptimal levels of O2 is considered to be due to photorespiration. Analysis of a range of developmental stages (along the leaf blade and at different leaf ages and positions) showed that the degree of inhibition of photosynthesis by supraoptimal levels of O2 increased rapidly once the ribulose-1,5-bisphosphate carboxylase/oxygenase and chlorophyll contents were below a critical level and was similar to that of C3 plants. Tissue having a high sensitivity of photosynthesis to O2 may be less effective in concentrating CO2 in the bundle sheath cells due either to limited function of the C4 cycle or to higher bundle sheath conductance to CO2. An analysis based on the kinetic properties of ribulose-1,5-bisphosphate carboxylase/oxygenase was used to predict the maximum CO2 level concentrated in bundle sheath cells at a given degree of inhibition of photosynthesis by supraoptimal levels of O2.